Comparative study of the physico-chemical properties of rice and corn starches grown in Indian temperate climate - Abida Ali; Touseef Ahmed Wani; Idrees Ahmed Wani; Farooq Ahmad Masoodi (Journal of the Saudi Society of Agricultural Sciences)
Starches isolated from the rice (Jhelum and Kohsar) and corn (PS-43 and Shalimar-maize) cultivars were studied for their physico-chemical and morphological properties. Physico-chemical properties such as composition, water and oil absorption capacity, swelling power, syneresis, freeze–thaw stability and light transmittance showed significant differences among the starches. Amylose contents of starches separated from the Jhelum and Kohsar rice cultivars and PS-43 and Shalimar-maize corn cultivars were 6.33%, 4.90%, 7.52% and 8.09%, respectively. The granular size varied from 5.2 to 5.9 μm for rice starches and 11.4–12.0 μm for corn starches. Transmittance value of gelatinized pastes from all starches progressively decreased up to the 2nd day during refrigerated storage, except Kohsar rice starch which lost its clarity significantly up to 3rd day of storage. The pasting property revealed peak, breakdown and setback viscosity which were in the range of 2479–3021 cP, 962–1713 cP and 1293–2003 cP respectively.